Adding whey and fishmeal to swine finishing diets - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred fifty finishing pigs were studied to evaluate the effect of adding whey and/or fishmeal to a sorghum grain-soybean meal basal swine diet. No significant effects due to treatment were observed on rate of gain, daily feed intake, or feed per lb. of gain for finishing pigs.
Keywords: Swine; Whey; Fishmeal; Finishing diets